2014
DOI: 10.1590/s0100-67622014000300013
|View full text |Cite
|
Sign up to set email alerts
|

Antagonismo de Trichoderma SPP. E Bacillus subtilis (UFV3918) a Fusarium sambucinum em Pinus elliottii engelm

Abstract: RESUMO -Pinus elliottii é uma espécie de importância no setor florestal e apresenta vulnerabilidade na qualidade sanitária de suas sementes, especialmente pela associação de Fusarium spp., responsável por perdas de plântulas no viveiro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
8
0
6
Order By: Relevance
“…son muy semejantes a los obtenidos por Aponte et al [41] con cepas ensayadas para el biocontrol in vitro de diferentes patógenos del suelo, incluido Fusarium; también coinciden con los de Ríos et al [42], quienes reportan inhibición de crecimiento de F. oxysporum en más del 50% con cepas nativas de Trichoderma (Figure 1 Bacillus. Los resultados de esta investigación también coinciden con los de Maciel et al [45], ya que reportaron que cepas nativas de Trichoderma spp. y B. subtilis fueron antagonistas contra F. sambucinum, señalando que esta acción fue más pronunciada cuando se utilizó Trichoderma spp., el cual inhibió en más de 60% a las colonias del fitopatógeno.…”
Section: Confrontaciones In Vitrounclassified
“…son muy semejantes a los obtenidos por Aponte et al [41] con cepas ensayadas para el biocontrol in vitro de diferentes patógenos del suelo, incluido Fusarium; también coinciden con los de Ríos et al [42], quienes reportan inhibición de crecimiento de F. oxysporum en más del 50% con cepas nativas de Trichoderma (Figure 1 Bacillus. Los resultados de esta investigación también coinciden con los de Maciel et al [45], ya que reportaron que cepas nativas de Trichoderma spp. y B. subtilis fueron antagonistas contra F. sambucinum, señalando que esta acción fue más pronunciada cuando se utilizó Trichoderma spp., el cual inhibió en más de 60% a las colonias del fitopatógeno.…”
Section: Confrontaciones In Vitrounclassified
“…in soybean [16], Trichoderma spp. and Bacillus subtilisin the control of Fusarium sambucinum in Pinus elliottii seedlings [17] and Bacillus subtilis in the control of Fusarium graminearum in wheat and barley [18]. However, there is lack of information regarding the treatment of seeds with biocontrol agents in cotton.…”
Section: Introductionmentioning
confidence: 99%
“…In their pioneering study on imported seeds of several Pinus species, Lasca et al (1971) demonstrated for the first time the presence of fungi in their seeds, including Pestalotia, Fusarium, Mucor, Aspergillus, Trichothecium, Alternaria, Diplodia, Botryodiplodia, Helminthosporium, Chaetomium, Rhizopus, Neurospora, and Penicillium. Recently, the quarantine pest Fusarium circinatum was detected in pine seedlings from imported seeds (Pfenning et al, 2014). Nevertheless, the health quality of pine seeds has been little studied in Brazil (Santos et al, , 2015Maciel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the study on the risk of using imported pine seeds (Pfenning et al, 2014), the few works performed in Brazil with national pine seeds have shown the association of several Fusarium species with pine seed rot and damping-off (Maciel et al, 2014;Homechin et al, 1986;. In the 1980s, F. moniliforme, F. oxysporum and F. semitectum were reported in seed lots of Pinus taeda and Pinus elliottii var.…”
Section: Introductionmentioning
confidence: 99%